Research on Social Participation Level of Religious Culture and Ethics Teacher Candidates in Turkey - Abdulkadir Cekin (Journal of Education and Learning (EduLearn), 2016)
Social participation is a very important skill in the context of socializing students. With the crucial process is likely to be related to students' social abilities, it is known social participation to be required some special educational activities. The aim of the research is to examine the social participation level of religious culture and ethics teacher candidates and to determine whether this level changes or not related to gender and high school graduation. The sample of the study is 222 teacher candidates at Kastamonu University, Faculty of Education, Department of Religious Culture and Ethics Teaching. General scanning method was used in this research. At the end of the research, it was found that the teacher candidates' social participation levels are high, they have confidence in themselves about the participation in social activities, there has occurred a significant differentiation in this level with regard to gender, but hasn't occurred a significant differentiation with regard to high school graduation.